2005
DOI: 10.1128/aem.71.9.5089-5097.2005
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Hop-Sensitive Variant of Lactobacillus lindneri and Identification of Genetic Markers for Beer Spoilage Ability of Lactic Acid Bacteria

Abstract: We have isolated a hop-sensitive variant of the beer spoilage bacterium Lactobacillus lindneri DSM 20692. The variant lost a plasmid carrying two contiguous open reading frames (ORF s) designated horB L and horC L that encode a putative regulator and multidrug transporter presumably belonging to the resistance-nodulation-cell division superfamily. The loss of hop resistance ability occurred with the loss of resistance to other drugs, including ethidium bromide, novobiocin, and cetyltrimethylammonium bromide. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
111
1
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 66 publications
(121 citation statements)
references
References 38 publications
5
111
1
2
Order By: Relevance
“…The strains were subjected to the horA-or horCspecific PCR as described previously 15,17 . The primers for PCR are listed in Table I.…”
Section: Detection Of the Hora And Horc Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…The strains were subjected to the horA-or horCspecific PCR as described previously 15,17 . The primers for PCR are listed in Table I.…”
Section: Detection Of the Hora And Horc Genesmentioning
confidence: 99%
“…Although this approach can rapidly determine whether detected isolates belong to the wellknown beer-spoilage species, the species-specific methods are not only unable to determine the intra-species differences in beer-spoilage ability but are also incapable of detecting previously uncharacterized beer-spoilage species. Based on our previous results, that all of the investigated beer-spoilage strains belonging to four beer-spoilage species have either or both of the horA and horC homolog, we have recently suggested that the combined use of horA and horC is useful for evaluating the beer-spoilage ability of LAB in a species-independent manner 15,17 . Therefore P. inopinatus LA20 and the three L. backi strains isolated in this study were examined for the presence or absence of the horA and horC genes.…”
Section: Detection Of the Hora And Horc Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…As for species-independent genetic markers, horA and horC have been demonstrated to confer hop resistance on LAB 46,90 , and it has been suggested that these two hop-resistance genes transfer horizontally between LAB, transforming nonspoilage strains into spoilage ones 109 . The horA and horC genes are highly specific genes to beer spoilage LAB at the strain level, and the presence or absence of these genetic markers was shown to highly correlate with the beer spoilage ability of LAB strains 36,92,107 . In fact, it was proposed that the horizontal acquisitions of hop resistance genes have been implicated in the emergence and spread of beer spoilage LAB through the history of beer brewing 102 .…”
Section: Quality Control Of Beer Spoilage Labmentioning
confidence: 99%
“…Among them the most important spoilage organisms are, according to brewing literature, L. brevis, L. lindneri, L. paracollinoides and P. damnosus 2,30,32,34 . In addition, L. backi and P. inopinatus have been reported as potential beer spoilers 7,22,33 .…”
Section: Introductionmentioning
confidence: 99%